2007
DOI: 10.1128/jvi.00465-07
|View full text |Cite|
|
Sign up to set email alerts
|

Compensatory Mutation Partially Restores Fitness and Delays Reversion of Escape Mutation within the Immunodominant HLA-B*5703-Restricted Gag Epitope in Chronic Human Immunodeficiency Virus Type 1 Infection

Abstract: HLA-B*5703 is associated with effective immune control in human immunodeficiency virus type 1 (HIV-1) infection. Here we describe an escape mutation within the immunodominant HLA-B*5703-restricted epitope in chronic HIV-1 infection, KAFSPEVIPMF (Gag 162-172), and demonstrate that this mutation reduces viral replicative capacity. Reversion of this mutation following transmission to HLA-B*5703-negative recipients was delayed by the compensatory mutation S165N within the same epitope. These data may help explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
139
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(150 citation statements)
references
References 33 publications
9
139
2
Order By: Relevance
“…Broadly neutralizing antibodies that target conserved viral epitopes may induce escape mutations in the virus that affect viral replicative fitness, as has been described for CD8 T cells (44)(45)(46). Structural and functional studies of the VRC01 class of antibodies indicate that they closely mimic the CD4 interaction with gp120 and bind to a conserved epitope that overlaps contact residues of the CD4 receptor (26,42,43,49,66).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Broadly neutralizing antibodies that target conserved viral epitopes may induce escape mutations in the virus that affect viral replicative fitness, as has been described for CD8 T cells (44)(45)(46). Structural and functional studies of the VRC01 class of antibodies indicate that they closely mimic the CD4 interaction with gp120 and bind to a conserved epitope that overlaps contact residues of the CD4 receptor (26,42,43,49,66).…”
Section: Discussionmentioning
confidence: 94%
“…Diminished viral replication after escape from T-cell immune pressure has been well documented for CD8 responses to the conserved Gag protein (44)(45)(46); however, it is less clear if the same is true for Env-targeting antibodies. It has been observed that mutations in CD4bs residues at the end of loop V5 that abrogate binding to anticore antibodies subsequently decrease viral fusion as well as viral infectivity (47), and there is evidence that in vivo antibody escape mutations in env can affect replication capacity (4,14,48).…”
mentioning
confidence: 99%
“…Positive selection pressure from the host immune system, which drives the selection of escape mutations (3,18), is responsible for some of these changes (12). However, others may be due to genetic drift or to changes in the amino acid sequence that compensate for any loss of core polypeptide function associated with the escape mutations (7,23). The full repertoire of common escape mutations in HBV polypeptides has not been defined, partly because the strong influences of both the viral genotype and host genetics on the immune response (26) make specific virus-host interactions difficult to identify in complex populations.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive studies have identified several dominant epitope targets of CD8 T cells that are presented by these HLA alleles, and revealed that recognition of those epitopes in the HIV gag protein by CD8 T cells contributes to limiting the HIV viral load in plasma. The same studies have revealed a high frequency of escape mutations in those epitopes, with concomitant decrease in viral fitness, which also contributes to limiting the level of the HIV viral load (Crawford et al 2007, 2009; Goepfert et al 2008). That the observed mutations represent escape from CD8 T cell recognition is supported by a high rate of reversion to the ancestral sequence in the involved epitopes when HIV is transmitted to an individual lacking a protective HLA allele.…”
Section: 2 Antigenic Variation In Human Pathogensmentioning
confidence: 85%
“…Although antibodies and CD8 T cell responses are both directed against multiple HIV proteins, these two mechanisms of immunity have distinct effects, depending on the antigenic target: antibody responses drive antigenic variation of the HIV surface envelope glycoprotein (Hraber et al 2015), while CD8 T cell responses drive antigenic variation of the HIV internal gag protein (Crawford et al 2007, 2009; Goepfert et al 2008). …”
Section: 2 Antigenic Variation In Human Pathogensmentioning
confidence: 99%